Do Work-Life Balance and Job Satisfaction Drive Employee Performance? Evidence from an Indonesian Local Government - Pebiy Pebrianti; Erwin Erwin; Anis Anshari Mas’ud (Universitas Negeri Gorontalo, 2026)
Purpose: This study examines the effect of work–life balance (WLB) on employee performance, with job satisfaction as a mediating variable, in the public-sector context of the Majene Regency Local Government, IndonesiaDesign/Methodology/Approach: Although previous studies have linked Work-Life Balance (WLB) to performance, the existing evidence mostly comes from the private sector, while local government settings are still underexplored. A quantitative survey was conducted by distributing questionnaires to 90 local government employees selected through stratified probability sampling. The data were analyzed using the measurement model (outer model) in SmartPLS version 3.Findings: The results show that WLB had no significant effect on either job satisfaction or employee performance, whereas job satisfaction had a positive and significant effect on employee performance. Because the conditions for mediation were not met, job satisfaction did not mediate the WLB performance relationship. These findings indicate that, in a bureaucratic public-sector environment, the expected benefits of WLB may weaken, while job satisfaction remains a robust predictor of performance.